Transcriptomic analysis and carbohydrate metabolism-related enzyme expression across different pH values in Rhizopus delemar - Jinpeng Liang; Yulan Chen; Yulan Chen; Sisi Li; Dongyang Liu; Dongyang Liu; Hong Tian; Quanju Xiang; Ke Zhao; Xiumei Yu; Qiang Chen; Hongzhu Fan; et al. (Frontiers in Microbiology, 2024)
IntroductionpH is one of the important factors affecting the growth and performance of microorganisms.MethodsWe studied the pH response and plant growth-promoting (PGP) ability of Rhizopus delemar using cultivation experiments and transcriptomics, and verified the expression profiles using quantitative real-time PCR.ResultspH affected the growth and PGP properties of R. delemar. At pH 7, the growth rate of R. delemar was rapid, whereas pH 4 and 8 inhibited mycelial growth and PGP ability, respectively. In the pot experiment, the plant height was the highest at pH 7, 56 cm, and the lowest at pH 4 and pH 5, 46.6 cm and 47 cm, respectively. Enzyme activities were highest at pH 6 to pH 7. Enzyme activities were highest at pH 6 to pH 7. Among the 1,629 differentially expressed genes (DEGs), 1,033 genes were up-regulated and 596 were down-regulated. A total of 1,623 DEGs were annotated to carbohydrate-active enzyme coding genes.DiscussionThe PGP characteristics, e.g., Phosphorus solubilization ability, of R. delemar were strongest at pH 7. The results provide useful information regarding the molecular mechanism of R. delemar pH response.